Peningkatan Imunitas Tubuh Melalui Tanaman Herbal Nusantara pada Komunitas Fathayat Nahdatul Ulama Kabupaten Muaro Jambi - Dwi Yunita Rahmadhani; Retty Octy (Jurnal Abdimas Kesehatan (JAK), 2022)
Corona Virus Disease (Covid) is a large family of viruses that cause illness ranging from mild to severe symptoms. Indonesia is the country with the highest number of Covid-19 cases in Southeast Asia and ranked 18th in the world with a total of 2,229,938 cases (2 July 2021). The most common symptoms of Covid-19 are fever, fatigue and a dry cough. Some patients may experience aches and pains, nasal congestion, runny nose, sore throat or diarrhea. These symptoms are usually mild and occur gradually. Some infected people do not experience any symptoms and do not feel any problems with their bodies. Diseases caused by viruses are generally self-limiting diseases that rely on the body's defenses. Because it has been widely campaigned to increase the body's resistance to prevent contracting viral infections, and even if infected, the body will be strong against it. Therefore, community service activities aim to improve the quality of public health by providing information to increase immunity through Indonesian herbal medicines. This activity will be held in September 2021 – February 2022 at the Fathayat Nahdatul Ulama Community at the Nurul Iman Islamic Boarding School, Muaro Jambi district. The target in this activity is the women of the Fathayat Nahdatul Ulama Community, Muaro Jambi district. The minimum number of participants is 50 people. This service activity received extraordinary enthusiasm from the participants as evidenced by the presence of all participants from the beginning to the end of the activity and the feedback from participants in the form of questions or experiences from participants in the material on increasing body immunity with herbal plants.